2009
DOI: 10.1017/s0033291709005236
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to depression: what is the role of stress genes in gene × environment interaction?

Abstract: Vulnerability to depression has been linked to the interaction of genetic predisposition with stressful life events. This review considers the associations between serotonergic and hypothalamic-pituitary-adrenal (HPA) systems. We follow the standpoint of a previous Editorial Review ( Bhagwagar & Cowen, Psychological Medicine 2008, 38, 307-313) and consider another possible mechanism of vulnerability to depressive disorder, that is we suggest that the gener environment interaction involves complex participati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 30 publications
(32 reference statements)
1
31
0
1
Order By: Relevance
“…There is evidence for all three routes in the development of depression. Firstly, altered HPA-axis activity and altered cortisol response has been found to be associated with increased risk for developing depression (Burke et al 2005;Cowen 2010;Harkness et al 2011;Luby et al 2004) and altering cognitive processes (El Hage et al 2009;Erickson et al 2003;Huffziger and Kuehner 2009). Furthermore, an interaction between a serotonin transporter promoter polymorphism (5-HTTLPR) and stress in the development of depression has been repeatedly reported with a recent meta-analysis of 54 studies showing strong evidence that 5-HTTLPR moderates the relationship between stress and depression, with the 5-HTTLPR s allele associated with an increased risk of developing depression under stress (P = .00002) (Karg et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence for all three routes in the development of depression. Firstly, altered HPA-axis activity and altered cortisol response has been found to be associated with increased risk for developing depression (Burke et al 2005;Cowen 2010;Harkness et al 2011;Luby et al 2004) and altering cognitive processes (El Hage et al 2009;Erickson et al 2003;Huffziger and Kuehner 2009). Furthermore, an interaction between a serotonin transporter promoter polymorphism (5-HTTLPR) and stress in the development of depression has been repeatedly reported with a recent meta-analysis of 54 studies showing strong evidence that 5-HTTLPR moderates the relationship between stress and depression, with the 5-HTTLPR s allele associated with an increased risk of developing depression under stress (P = .00002) (Karg et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Future longitudinal studies should now aim to validate such an approach and to determine how these risk factors interact with various "stress genes" to increase the risk of depression (Almeida et al, 2009b;El Hage et al, 2009). The use of a well-validated probabilistic matrix will contribute to guide the design of effective preventive measures to decrease the prevalence and incidence of depression in later life.…”
Section: N O D E P R E S S I O N M I N O R D E P R E S S I O N M a J mentioning
confidence: 99%
“…The leading explanation for this variability proposes that genetic variance modulates the effect of stress on the brain (9;10). Indeed, numerous studies have shown that persons with a specific genetic make-up are more prone to develop stress-related mental disorders after experiencing major life events like CA (11)(12)(13). Moreover, recent studies suggest that gene by stress interactions may be involved in inter-individual differences in local brain volume (14) and may also play a role in the onset of several psychiatric disorders, like bipolar disorder, schizophrenia, attention deficit hyperactivity disorder and depression (for review see (15)).…”
Section: Introductionmentioning
confidence: 99%